Connecting the dots: Linking technological, individual, organizational and environmental factors towards SMEs performance with the mediation role of e-commerce adoption - Maslichah, Maslichah; Diana, Nur (University of Islam Malang, 2022)
Despite the proven potential of e-commerce in generating business competitiveness and performance, small and medium enterprises (SMEs) adopting that particular technology in developing countries such as Indonesia remains relatively low. It is critical to evaluate the obstacles, expose them, and find a way to overcome the issue, especially as the recent global pandemic of COVID-19 has impacted this sector to a great extent. The impact of COVID-19 on Indonesian SMEs and how they are dealing with it are highlighted in this paper, which is quite scarce and insufficient to cover the gap. Using a survey of 278 SME owners and/or managers in Indonesia, our study aims to explore the influence of technological, individual, organizational, and environmental factors on SMEs' adoption of e-commerce and business performance. We use PLS to explore the relationships proposed in our framework model. The results of this study revealed that technological, individual, organizational, and environmental factors positively affect the adoption of e-commerce. The findings also confirmed that technological, organizational, and environmental factors are the determinant factors that affect Indonesian SMEs' performance. Interestingly, the study did not prove the direct effect of individual characteristics on performance. It indicates that the performances and innovativeness of SMEs within our study are more rooted in their organizational setting rather than individual.